2014
DOI: 10.1126/science.1253253
|View full text |Cite
|
Sign up to set email alerts
|

Stellar activity masquerading as planets in the habitable zone of the M dwarf Gliese 581

Abstract: The M dwarf star Gliese 581 is believed to host four planets, including one (GJ 581d) near the habitable zone that could possibly support liquid water on its surface if it is a rocky planet. The detection of another habitable-zone planet--GJ 581g--is disputed, as its significance depends on the eccentricity assumed for d. Analyzing stellar activity using the Hα line, we measure a stellar rotation period of 130 ± 2 days and a correlation for Hα modulation with radial velocity. Correcting for activity greatly di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
214
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(221 citation statements)
references
References 31 publications
6
214
1
Order By: Relevance
“…The sensitivities of the future instruments, such as ESPRESSO (Echelle SPectrograph for Rocky Exoplanet-and Stable Spectroscopic Observations) for the Very Large Telescope and CODEX (COsmic Dynamics and EXo-earth experiment) for the European Extremeley Large Telescope, aim to resolve Doppler shifts to as low as 0.1 m s −1 (Pepe et al 2014) and 0.01 m s −1 (Pasquini et al 2010) respectively. As mentioned earlier, the resultant noise from stellar activity in Sun-like stars is not considered in our assessment but will need to be taken into account at such low detection limits to avoid false positives (Robertson et al 2014). …”
Section: Searching For Exo-earths In Single Jupiter Systemsmentioning
confidence: 99%
“…The sensitivities of the future instruments, such as ESPRESSO (Echelle SPectrograph for Rocky Exoplanet-and Stable Spectroscopic Observations) for the Very Large Telescope and CODEX (COsmic Dynamics and EXo-earth experiment) for the European Extremeley Large Telescope, aim to resolve Doppler shifts to as low as 0.1 m s −1 (Pepe et al 2014) and 0.01 m s −1 (Pasquini et al 2010) respectively. As mentioned earlier, the resultant noise from stellar activity in Sun-like stars is not considered in our assessment but will need to be taken into account at such low detection limits to avoid false positives (Robertson et al 2014). …”
Section: Searching For Exo-earths In Single Jupiter Systemsmentioning
confidence: 99%
“…Evidence for intra-spectrum RV jitter Starspots cause significant jitter in radial velocity (RV) surveys for young planets (e.g. Donati et al 2014;Robertson et al 2014). The two-temperature model assumed that the hot and cool components shared the same v sin i and v z .…”
Section: The Limitation Of a Two-temperature Modelmentioning
confidence: 99%
“…To worsen the case, late-type M dwarfs are on average more active and display more stellar spots (e.g., Shkolnik et al 2009;Morin et al 2010;Shkolnik et al 2012;Malo et al 2014;Schmidt et al 2015), which can induce RV signals very similar to those of planetary companions (e.g., Queloz et al 2001;Paulson & Yelda 2005). Robertson et al (2014) demonstrated the importance of a careful consideration of stellar activity in exoplanet searches by demonstrating that the purported GJ581d habitable-zone exoplanet ) was most likely a false-positive signal caused by stellar spots. Overcoming this limitation is especially important in the search for very-low-mass companions that induce RV variations of low amplitudes (e.g., a few m s −1 ) comparable to stellar activity jitter.…”
Section: Introductionmentioning
confidence: 99%